Impact of selected phytogenic feed additives on performance, haematological, biochemical, and antioxidant enzyme responses in 64-week-old laying hens - Oluwafemi-Ayeni , Akinlolu (2025)
The effects of turmeric, ginger, and garlic powders on the performance, blood profile, serum biochemistry, and antioxidant properties of 64-week-old laying hens were evaluated. The study was carried out at the Teaching and Research Farm of the Department of Animal Production and Health, The Federal University of Technology, Akure (FUTA), Ondo State, Nigeria. A 12-week feeding trial was conducted with a total of 135 Isa Brown laying hens, arranged in a completely randomized design. Five diets were formulated for the prosecution: Diet 1 (control); Diet 2 (3.00% addition of turmeric); Diet 3 (3.00% addition of ginger); Diet 4 (turmeric and garlic at 2.25% and 0.75%, respectively); and Diet 5 (ginger and garlic at 2.25% and 0.75%, respectively). The proximate compositions of the phytogenic feed additives (PFAs) were determined as follows: moisture (5.03 – 7.50%); ash (3.26 – 6.11%); ether extract (7.39 – 14.58%); crude fiber (10.28 – 13.79%); crude protein (3.07 – 7.23%); and nitrogen-free extract (58.88 – 61.54%). The performance indices were not significantly influenced by the test diets (p> 0.05), except for hen-day production (HDP). The lowest HDP (57.50%) and feed conversion ratio (FCR) (2.37%) were observed in Diet 4. No significant differences were recorded among the haematological parameters and biochemical indices (p > 0.05). Glutathione peroxidase (GSH) activity was significantly highest (2.02 μM/mL) in birds fed Diet 2 (p < 0.05). The activities of catalase (0.80 μM/mg protein) and superoxide dismutase (60%) were significantly (p < 0.05) highest in birds on Diet 5. The results of this study indicate that PFAs do not exert adverse effects on the health of older laying hens; on the contrary, they help maintain productive performance and improve serum and antioxidant profiles.